Demographic Profile and Extra Intestinal Manifestations of Ulcerative Colitis in Pakistani population - Usman Ali, Jahangir Anjum, Sheraz Ahmed, Humaira Erum, Saadia Hamid, Nazia Akber Mir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: It is a systemic disorder. It begin in the rectum and later on extent to the other organs. Usually the involvement of other organ in addition to intestine is observed and the condition is called as extra intestinal manifestation. It is associated with high rate of morbidity and mortality. Study design: It is a retrospective study conducted in Mohtrama Benazir Bhutto Shaheed Medical College / Divisional Headquarters teaching hospital Mirpur Azad Kashmir for the duration of six months from February 2022 to July 2022. Material and Methods: There were total 72 males that participated in this study and 48 females. The age distribution of the patients is. Most of the patients belonged to age group from 20 to 39 years followed by group 40-59 where 22 patients were reported. This study was approved by the hospital review board committee. The participants were aware of the study objective. The written consent was signed by the participants. The SPSS was used for the statistical analysis. Results: Extra-intestinal manifestations of the patient were analyzed and it was found that in 24% of the patient’s musculoskeletal symptoms were present. Sacroilitis was observed in 12.1% of the patients as the most commonly found symptom. Peripheral arthritis was also reported in 7.3% of the patients. Episcleritis was present in case of 2.1% of the patients. Conclusion: It is concluded that the peak age of patients included in this study with Ulcerative colitis is according to the other European and Asian countries, However, the second peak of Ulcerative colitis was missing unlike in some European studies. Extra intestinal Manifestations were quite low. Keywords: Inflammatory bowel disease and extra intestinal manifestation.